(untitled) (Bioscience Journal, 2015)
Intake and performance of goats fed exclusively forages Tifton 85, mulberry or leucaena were simulated to verify which nutrients limit performance. Simulations were performed using the nutritional model similar to Cornell Net Carbohydrate and Protein System (CNCPS) with modifications related to the kinetic attributes of digestion and feed passage. The animal category chosen to perform the simulations was female Saanen goats in growing phase between weaning and mating, with 20 kg of body weight and 150 g of daily gain. The intake of 0.870 kg/day of Tifton 85 was adopted for performance simulations because in this point caused rumen fill and also attended the energy requirement of the animal. For performance simulations of mulberry, the amount of dry matter intake of 0.580 kg/day was adopted based on average intake obtained from the study of Sabino Jr. (1996) and simulations for leucaena used the intake of 0.220 kg/day, corresponding to 30g/100g of dry matter intake that would supply the energy requirement of these female goats. The limiting factor of performance of Saanen female growing goats fed exclusively Tifton 85 or mulberry is the metabolizable protein and not the energy. The intake of leucaena exclusively would be able to supply the requirement of metabolizable protein to promote the target weight gain of 150 g/day. The forages do not present perfect synchronization between carbohydrates and proteins, demonstrated by the positive ammoniacal balance in rumen environment that indicates an excess of nitrogen compounds supplied by these feed.